2022
DOI: 10.1186/s13578-022-00892-6
|View full text |Cite
|
Sign up to set email alerts
|

PEX5R/Trip8b-HCN2 channel regulating neuroinflammation involved in perioperative neurocognitive disorders

Abstract: Background Clinical and animal studies demonstrated that neuroinflammation from anesthesia (sevoflurane) is the main contributor to cause perioperative neurocognitive disorders (PND). Recently, it was reported that microglia respond to hyperpolarization-activated cyclic nucleotide-gated (HCN) channels, which was the target of sevoflurane. Whether HCN channels are involved in the induction of neuroinflammation after sevoflurane exposure is still unclear. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Although, xiangdong Chen, et al. (2022) reported that in cognitive‐impaired rats inhaling sevoflurane, there is an upregulation of neuroinflammation (IL‐1β, IL‐6, and TNF‐α) in the hippocampus 55 . The effect of sevoflurane on the expression of inflammatory factors may be related to the concentration and duration of anesthesia, as well as organ specificity 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Although, xiangdong Chen, et al. (2022) reported that in cognitive‐impaired rats inhaling sevoflurane, there is an upregulation of neuroinflammation (IL‐1β, IL‐6, and TNF‐α) in the hippocampus 55 . The effect of sevoflurane on the expression of inflammatory factors may be related to the concentration and duration of anesthesia, as well as organ specificity 56 .…”
Section: Discussionmentioning
confidence: 99%
“…According to previous work, the i.c.v. injection site was located as: AP (anteroposterior) = −1.2 mm, ML (mediolateral) = 1.8 mm, and DV (dorsoventral) = 4.0 mm [ 15 ]. Then, following SIN establishment by sevoflurane exposure, these rats were assigned to two groups: the Sevo-IgG and Sevo-C1q groups.…”
Section: Methodsmentioning
confidence: 99%
“…As reviewed, this inflammasome mediates the secretion of proinflammatory cytokines such as IL-1β and IL-18. Similarly, exposure to sevoflurane has been shown to result in hippocampal microglial activation with elevated IL-1β, IL-6, and TNF-α, mediated through HCN2 channel inhibition (188). Specifically, sevoflurane resulted in downregulation in PEX5R/Trip8b-HCN2 channels in microglia and neurons while causing neuroinflammation in the rodent cortex and hippocampus.…”
Section: Inhalational Anestheticsmentioning
confidence: 98%